An Essential Role for a Small Synaptic Vesicle-Associated Phosphatidylinositol 4-Kinase in Neurotransmitter Release - Wiedemann, Claudia (J Neurosci, 1998)
Glutamate release from nerve terminals is the consequence of Ca(2+)-triggered fusion of small synaptic vesicles with the presynaptic plasma membrane. ATP dependence of neurotransmitter release has been suggested to be founded, in part, on phosphorylation steps preceding membrane fusion. Here we present evidence for an essential role of phosphatidylinositol phosphorylation in stimulated release of neurotransmitter glutamate from isolated nerve terminals (synaptosomes). Specifically, we show that a phosphatidylinositol 4-kinase (PtdIns 4-kinase) activity resides on nerve terminal-derived small synaptic vesicles (SSVs) and that inhibition of the PtdIns 4-kinase activity in intact synaptosomes leads to attenuation of the evoked release of glutamate. The attenuation of transmitter release is reversible and correlates with respective changes in intrasynaptosomal PtdIns 4-kinase activity. Because only the Ca(2+)-dependent release of glutamate is affected, regulation appears to be at the level of exocytosis. Taken together, our data imply a mandatory role for PtdIns 4-kinase and phosphoinositide products in the regulated exocytosis of SSV in mammalian nerve terminals.